Future flight decks: impact of +Gz on touchscreen usability - Avsar, Huseyin; Fischer, Joel E.; Rodden, Tom (2016)
Future flight deck designs from various avionics manufacturer incorporate touchscreen technology. There is little published research investigating the impact of inflight vibrations and increased G-Force (+Gz) on touchscreen usability. A Fitts’ law experiment was conducted to understand the effect of +Gz on touchscreen usability. 2-Gz and 3-Gz conditions were simulated with a weight-adjustable wristband. Empirical results and subjective ratings showed a large impact of +Gz on performance and fatigue indices. While the simulated +Gz increased linearly, throughput decreased exponentially, and movement time increased exponentially. This was also reflected by subjective ratings across all conditions. Findings suggest to transfer the experimental setting into a more realistic environment (human centrifuge) where ecological validity can be achieved.